Authority, states and persons: in the search for optimal reconciliation - Greenfield, E; Shivi Greenfield (2011)
The problem of legitimate authority is widely regarded as fundamental to moral and political philosophy. This thesis aims to explain what the problem precisely is, and to offer a practical method for solving it. The starting point is a claim about the phenomenology of the person as an inherently authoritative agent: we are persons, as distinct from mere ‘things’, by virtue of the authority we possess over ourselves. This claim explains, I argue, why there is a problem of legitimate authority – why the exercise of state authority stands in need of justification – and what the problem precisely is: given the inherent tension between the authority of the state on the one hand, and the self-governing authority of persons on the other, the problem of legitimate authority is essentially that of creating the conditions for optimal reconciliation between them. The bulk of the thesis is devoted to a search for a solution to this problem. The ideal solution lies in developing a concept which I call the Authorization Principle. In its most basic form, the principle states that the exercise of state authority is legitimate only when it is exercised to enforce arrangements that all citizens authorize the state to enforce. The conclusion of the thesis is that the principle should be formulated as follows: The exercise of state authority is legitimate insofar as it is exercised within the provisions of a constitutional arrangement constructed through a process that gives equal weight to all the epistemically undefeated concerns in the society regarding the conditions necessary for persons to exercise personal authority. The solution proposed in the thesis for the problem of legitimate authority has three important implications. The first is that it is entirely within the capacity of ordinary democratic societies to solve the problem. The second is that there is no single legitimate way to govern a society. Standards for the legitimate use of state authority are in some way indexed to culture, ability and resources as well as to other aspects of a society’s unique circumstances. The third is that a society cannot settle the problem of legitimate authority once and for all. The state’s arrangement will require revision every so often in order to maintain the legitimacy of state authority.